Injetividade de aplicações semialgébricas - Rego, Helano dos Santos Campelo (2016)
Motivated by conjecture Jacobian, it presents a change considering semi-algebraic maps and interesting properties of the set of not proper points of F. Initially makes a general explanation of the topological concepts and semi-algebraic theory that will serve as the basis for a broad understanding of the main theorem, it presents even a brief historical introduction to some aspects interesting in the development of theory until now. For last it`s presented the theorem which deals with from the extension from local di eomorphisms to the global injectivity.